2011
DOI: 10.1007/s11224-011-9820-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surface curvature of aluminum nitride nanotubes on the adsorption of NH3

Abstract: Our main objectives are to address the following fundamental issues: (1) A density functional theory study on the structural and electronic properties of the zigzag singlewalled aluminum nitride nanotubes (AlNNTs) with various diameters, using B3LYP/6-31G* level of theory.(2) An ONIOM study on the curvature effect of AlNNTs on the NH 3 adsorption process using B3LYP/6-31G* and semiempirical AM1 approaches. Furthermore, a potential energy surface is calculated for NH 3 moving toward AlNNT surface. In contrast t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(20 citation statements)
references
References 36 publications
(36 reference statements)
0
20
0
Order By: Relevance
“…B3LYP, has the most generality and predictive capacity providing a sufficiently accurate description of finite-size nanotubes [15][16][17][18][19]. As we have recently showed, during the NH 3 adsorption process, a single NH 3 molecule dissociates into an -H atom and an -NH 2 group at the open ends of BNNTs [10].…”
Section: Resultsmentioning
confidence: 99%
“…B3LYP, has the most generality and predictive capacity providing a sufficiently accurate description of finite-size nanotubes [15][16][17][18][19]. As we have recently showed, during the NH 3 adsorption process, a single NH 3 molecule dissociates into an -H atom and an -NH 2 group at the open ends of BNNTs [10].…”
Section: Resultsmentioning
confidence: 99%
“…The sign of V(r) depends on whether the effects of the nuclei or the electrons are dominant at any point (Beheshtian et al 2011b). So far, the MEP has frequently been used for the interpretation of the electrical properties of various materials (Peralta-Inga et al 2003;Ahmadi et al 2011;Politzer et al 2005Politzer et al , 2001. MEP plots in Fig.…”
Section: Molecular Electrostatic Potential Analysismentioning
confidence: 99%
“…[13][14][15][16][17] In previous papers the adsorption of various gases such as SO 2 , H 2 S, CO 2 and CO on surfaces of nanostructures have been investigated. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Zaboli and et al 35 the adsorptions of the H 2 S, H 2 Se and SO 2 molecules on the surface of fullerene by the density functional theory investigated. Obtained results shown that, the adsorption energy amounts of gas molecule were short, so, the sensor were possess at short recovery times.…”
Section: Introductionmentioning
confidence: 99%